Caring for Thai older persons with long-term care needs - KNODEL, John (Institutional Knowledge at Singapore Management University, 2016)
Thailand is experiencing more acute population aging than most developing Asian countries. Its population aged 60 and older is anticipated to grow from 10% in 2000 to 38% by 2050. Meanwhile, the oldest-old population that is most likely to require long-term care (LTC) is estimated to increase tenfold during the first half of the 21st century. Family has remained a linchpin of support for Thai elders with LTC needs. Given population aging and other demographic trends such as smaller family size, migration of adult children, and lengthening survival at older ages, policy makers are concerned how such socio-demographic changes may have implications for familial support for older persons with LTC needs and in turn, the wellbeing of the elderly. The Thai government has thus far played a limited role in addressing LTC. While Thailand's recent National Plan for Older Persons recognizes the importance of LTC management, empirical evidence to support such policy planning remains lacking. This study provides a situation analysis of recent LTC needs among older persons in Thailand based on nationally representative surveys. Specifically, we examine prevalence of self-care disability (i.e., elderly with difficulty in activities of daily living) and how such disability varies by socio-demographic characteristics of older persons. Moreover, we assess patterns of caregiving, whether care needs are met, and who primarily takes care of older Thais with LTC needs. We are particularly interested in whether older persons with ADL disability take care of him/herself, or whether they have family members (spouse, children, other relatives) or others (friends, paid carers) as the main caregiver. Furthermore, we examine how types of familial and non-familial caregivers and the quality of caregiving (measured by caregiving knowledge) are associated with the wellbeing of older persons with self-care disability. Our analysis is based primarily on the 2014 Survey of Older Persons in Thailand (SOPT), which is the fifth in a series of Thai government surveys of older persons. The sample consists of 34,173 persons aged 60 and over, of which, 2,020 report having self-care disability.